Social customer relationship management (Social-CRM) in the era of Web 4.0 - Ammari, Nedra Bahri, 1973- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series., 2022)
"This book is for those who wish to improve their understanding of the strategic role of marketing 2.0, digital customer experience and social customer relationship management on social networks and the importance of social networks to build loyalty in the web 4.0 era"--